Study on some blood biochemical parameters in postpartum crossbred cows treated with GnRH and PGF2alpha - SHESHAPPA, H; HONNAPPAGOL, S S; TANDLE, M K; AMANULLAH, MOHD (The Indian Journal of Animal Reproduction, 2023)
The levels of various blood biochemical parameters viz. plasma calcium, inorganic phosphorous andtotal protein were marginally higher in the GnRH and GnRH + PGF 2alpha . treated groups than the control. TheAcetone level during the early postpartum period, however, was lower in treated than control group indicating beneficial effect of treatment..
Keywords: GnRH; PGF2alpha; calcium; phosphorus; protein; cow